2011
DOI: 10.1121/1.3518780
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the balloon as an impulse source

Abstract: Many cross-language and L2 speech perception studies have been conducted on English sounds and a limited number of speakers or synthetic tokens have been used for auditory stimuli. The Spanish listeners of the present study were presented with natural tokens of Dutch vowels produced by males and females selected from the corpus reported in Adank et al. [(2004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Consequently, neither source complied with ISO requirements in the low-frequency range, while they satisfy the requirements in the high frequency range. In particular, Patynen et al 11 confirmed, as observed by Griesinger, 9 that the directivity pattern of a popped balloon is influenced by the pin-prick point. A low-frequency energy peak occurs in that direction while a high-frequency peak occurs in the opposite direction.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Consequently, neither source complied with ISO requirements in the low-frequency range, while they satisfy the requirements in the high frequency range. In particular, Patynen et al 11 confirmed, as observed by Griesinger, 9 that the directivity pattern of a popped balloon is influenced by the pin-prick point. A low-frequency energy peak occurs in that direction while a high-frequency peak occurs in the opposite direction.…”
supporting
confidence: 50%
“…8,9 So, sound sources like the "clapper" 10 or the classic balloons 11 have been carefully characterized both in terms of spectrum and directivity. In the first case, directional fluctuations of about 3 dB appeared in the low frequency range, increasing to 5 dB above 1 kHz.…”
mentioning
confidence: 99%
“…28 Small differences can be detected between different excitation techniques in the measurement of reverberation time, 29 and these differences are mainly encountered at the lowest frequencies for a balloon-pop. 30 The average occupied reverberation time, from the 500 Hz to 2 kHz octave bands, and over four sourcemicrophone positions, RT mean,500-2 kHz , was obtained for each occupied classroom.…”
Section: B Measurement Of the Acoustical Parameters In The Classroomsmentioning
confidence: 99%
“…Recent studies [11] analysed the properties of balloons and revealed that theya re, in general, unsatisfactory sound sources. Our owne xperiments, presently unpublished, reveal that industrial-grade firecrackers provide very good omnidirectionality,repeatability and areasonably flat spectrum (unchanging with direction and distance, and hence easily perfectly flattened in post-processing).…”
Section: Test Signal and Sound Sourcementioning
confidence: 99%